Answer:
a. (-3, 2).
b. √65
c. (x + 3)^2 + (y - 2)^2 = 65
Step-by-step explanation:
a. The center is the midpoint of the diameter PQ.
= (-10+4)/2, (-2+6)/2
= (-3, 2).
b. The radius is the distance from the center to a point on the circle.
Take the point (4, 6):
The radius = √((-3-4)^2 + (2-6)^2)
= √65.
c. The equation of the circle is:
Using the standard form
(x - h)^2 + (y - k)^2 = r^2 where (h, k) is the center and r = the radius:
it is (x - (-3)^2 + (y - 2) = 65
= (x + 3)^2 + (y - 2)^2 = 65.
The answer would be 6, 0.5
Answer:
5:4
Step-by-step explanation
If your shoes to flip-flops are 10:8 then the starting ratio will be 10:8 but 10 and 8 are both divisible to 2 so you can simplify 10:8 to 5:4
Answer:
x=5 y=-6
Step-by-step explanation:
3x+y=9 ------eqn1
y=4-2x -------eqn2
using substitution
put y=4-2x into eqn1
3x+4-2x=9
x=5
put x=5 into eqn2
y=4-2(5)
y=4-10
y=-6
Answer:
8r and -4r
3s and -3s
second andd fourth answer